QUALITATIVE AND QUANTITATIVE ANALYSIS OF PARACETAMOL CONTAMINATION IN RHEUMATIC PAIN TRADITIONAL MEDICINE - Desy Ayu Irma Permatasari; Rini Setyowati; Muladi Putra Mahardika (Jurnal Farmasi Sains dan Praktis, 2022)
Analgesic drugs are often added illegally in rheumatic pain traditional medicine. Paracetamol is one of chemical drugs that have a large possibillity to be added in rheumatic pain traditional medicine. The aims this research were to know paracetamol and concentration of paracetamol in rheumatic pain traditional medicine in Borobudur District. This research is experimental research, the analysis data were used microsoft excel and linear regression. Qualitative analysis method using organoleptic test to description the sample, TLC test to evaluation Rf value and FTIR test for characterization. Quantitative analysis method using LC-MS test to know the paracetamol concentration contained on the rheumatic pain traditional medicine. Organoleptic test the results show description the shape, color, smell and taste of sample A, B and C. The results of the TLC evaluation showed sample A and B were positive, indicated by a purple spot and the Rf value of the sample was exactly same compared to Rf value of standard paracetamol, while sample C is negative. The result of the FTIR spectra showed that sample A and B have same functional group as the standard paracetamol, while sample C showed none. LC-MS test results after calculating the concentration in samples A and C the concentration was obtained < 4,4 μg/kg below the Detection Limit (LoD): 4,4 μg/kg, while sample B the concentration was obtained 2,22%. Based on the results of all three samples tested, the sample A and sample B were positively contaminated by chemical medicine paracetamol while sample C were negative.